Influence of the Microbial Metabolite Acetyl Phosphate on Mitochondrial Functions Under Conditions of Exogenous Acetylation and Alkalization - Natalia V. Beloborodova; Nadezhda I. Fedotcheva (Metabolites)
Background. Acetyl phosphate (AcP) is a microbial intermediate involved in the central bacterial metabolism. In bacteria, it also functions as a donor of acetyl and phosphoryl groups in the nonenzymatic protein acetylation and signal transduction. In host, AcP was detected as an intermediate of the pyruvate dehydrogenase complex, and its appearance in the blood was considered as an indication of mitochondrial breakdown. In vitro experiments showed that AcP is a powerful agent of nonenzymatic acetylation of proteins. The influence of AcP on isolated mitochondria has not been previously studied. Methods. In this work, we tested the influence of AcP on the opening of the mitochondrial permeability transition pore (mPTP), respiration, and succinate dehydrogenase (SDH) activity under neutral and alkaline conditions stimulating the nonenzymatic acetylation using polarographic, cation-selective, and spectrophotometric methods. Results. It was found that AcP slowed down the opening of the mPTP by calcium ions and decreased the efficiency of oxidative phosphorylation and the activity of SDH. These effects were observed only at neutral pH, whereas alkaline pH by itself caused a decrease in these functions to a much greater extent than AcP. AcP at a concentration of 0.5–1 mM decreased the respiratory control and the swelling rate by 20–30%, while alkalization decreased them twofold, thereby masking the effect of AcP. Presumably, the acetylation of adenine nucleotide translocase involved in both the opening of mPTP and oxidative phosphorylation underlies these changes. The intermediate electron carrier phenazine methosulfate (PMS), removing SDH inhibition at the ubiquinone-binding site, strongly activated SDH under alkaline conditions and, partially, in the presence of AcP. It can be assumed that AcP weakly inhibits the oxidation of succinate, while alkalization slows down the electron transfer from the substrate to the acceptor. Conclusions. The results show that both AcP and alkalization, by promoting nonmetabolic and nonenzymatic acetylation from the outside, retard mitochondrial functions.